Phytoplankton in headwater streams: spatiotemporal patterns and underlying mechanisms - Zeng, Chenjun; Xing, Ran; Huang, Bensheng; Cheng, Xiangju; Shi, Wenqing; Liu, Shufeng (Frontiers in Plant Science, 2023)
Phytoplankton are key members of river ecosystems wherein they influence and regulate the health of the local environment. Headwater streams are subject to minimal human activity and serve as the sources of rivers, generally exhibiting minimal pollution and strong hydrodynamic forces. To date, the characteristics of phytoplankton communities in headwater streams have remained poorly understood. This study aims to address this knowledge gap by comparing phytoplankton communities in headwater streams with those in plain rivers. The results demonstrated that within similar watershed sizes, lower levels of spatiotemporal variability were observed with respect to phytoplankton community as compared to plain rivers. Lower nutrient levels and strong hydrodynamics contribute to phytoplankton growth limitation in these streams, thereby reducing the levels of spatiotemporal variation. However, these conditions additionally contribute to greater phytoplankton diversity and consequent succession towards Cyanophyta. Overall, these results provide new insights into the dynamics of headwater stream ecosystems and support efforts for their ecological conservation.